2007
DOI: 10.1126/science.1146157
|View full text |Cite
|
Sign up to set email alerts
|

Hold Your Horses: Impulsivity, Deep Brain Stimulation, and Medication in Parkinsonism

Abstract: Deep brain stimulation (DBS) of the subthalamic nucleus markedly improves the motor symptoms of Parkinson's disease, but causes cognitive side effects such as impulsivity. We showed that DBS selectively interferes with the normal ability to slow down when faced with decision conflict. While on DBS, patients actually sped up their decisions under high-conflict conditions. This form of impulsivity was not affected by dopaminergic medication status. Instead, medication impaired patients' ability to learn from neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

96
914
7
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 986 publications
(1,025 citation statements)
references
References 34 publications
(67 reference statements)
96
914
7
8
Order By: Relevance
“…This suggests that the inhibition of normal behaviour related to obsessions and compulsions on the one hand and impulsivity on the other might be on opposite sides of a behavioural spectrum. STN DBS in PD induces cognitive impulsivity, but at the same time improves cognitive flexibility [40,49] and speeds up decisions under high-conflict conditions [107], so we propose that cognitive-behavioural disinhibition might help in improving the incapacity to make a decision because of permanent doubt, which is a core feature of OCD. Although OCD seems as an area of high potential application of DBS, clinical trials are needed to reach conclusions regarding the best anatomical target site for this condition.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 93%
“…This suggests that the inhibition of normal behaviour related to obsessions and compulsions on the one hand and impulsivity on the other might be on opposite sides of a behavioural spectrum. STN DBS in PD induces cognitive impulsivity, but at the same time improves cognitive flexibility [40,49] and speeds up decisions under high-conflict conditions [107], so we propose that cognitive-behavioural disinhibition might help in improving the incapacity to make a decision because of permanent doubt, which is a core feature of OCD. Although OCD seems as an area of high potential application of DBS, clinical trials are needed to reach conclusions regarding the best anatomical target site for this condition.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 93%
“…Worsening of dyskinesia or dystonia can appear during initial DBS programming sessions, but these symptoms decline after several hours of continuous stimulation. 160 Deep brain stimulation can generate cognitive side effects as well, including mood changes, 161 depression, 162 decreased working memory performance, 163,164 impulsivity, 165 and hallucinations. 166 One explanation for the emergence of such cognitive side effects is that suprathreshold currents spread into nonmotor regions within the basal ganglia and thalamocortical networks.…”
Section: What To Avoid: Targets That Lead To Undesirable Side Effectsmentioning
confidence: 99%
“…Early studies on patients with idiopathic Parkinson's disease (iPD) have demonstrated that the subthalamic nucleus (STN) influences learning and attentional processes, which can either be improved or impaired depending on the task (Jahanshahi et al 2000). More recently, the STN was suggested as relay in the decision making process by providing an inhibitory signal to prevent premature execution of responses in conflicting decisions (Mink 1996;Aron and Poldrack 2006;Frank et al 2007;Thobois et al 2007;Ballanger et al 2009 (Frank 2006) are critical in the early phase of skill acquisition. In particular, STN activity was predicted in Frank's model to increase during trial repetitions '25-60' during early decision making repetitions (Frank 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, STN activity was predicted in Frank's model to increase during trial repetitions '25-60' during early decision making repetitions (Frank 2006). However, the experimental paradigms used in healthy subjects and iPD patients with subthalamic nucleus deep brain stimulation (STN-DBS) were independent of the learning process and included a well-trained probabilistic selection task (Frank et al 2007), a random number generation task (Thobois et al 2007) and a Go/NoGo task (Aron and Poldrack 2006;Ballanger et al 2009). …”
Section: Introductionmentioning
confidence: 99%